Strategi Peningkatan Penerimaan Pendapatan Pajak Restoran di Kota Tomohon - Ignatia Rosali Honandar; Frankie Jantje Hendrikus Taroreh; Maria Pusung (Jurnal Humanipreneur, 2023)
The aim of this research is to find out the mechanism for implementing restaurant tax revenue through e-SPTPD, find out the obstacles in implementing restaurant tax revenue through e-SPTPD and the strategies used to increase the implementation of restaurant tax revenue using e-SPTPD in the city of Tomohon. The research method used to analyze the research results is descriptive qualitative research with an exploratory approach. A total of 5 participants were chosen to be the source persons in this research. The research results show that the restaurant tax revenue mechanism using e-SPTPD in the city of Tomohon has been implemented well. The obstacles faced in receiving restaurant taxes using e-SPTPD are: low compliance and awareness of restaurant taxpayers; Restaurant taxpayer human resources who do not really understand the use of e-SPTPD; socialization regarding the use of e-SPTPD has not been evenly distributed; internet network problems and server errors; and tax payments that can only be made in cash at BSG. Meanwhile, the strategies implemented by BPKPD to increase restaurant tax revenues through e-SPTPD are: conducting outreach regarding the use of e-SPTPD to restaurant taxpayers; monitoring restaurant taxpayers; and giving awards or rewards to restaurant taxpayers.